2017
DOI: 10.1111/petr.12986
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse myocardial fibrosis among healthy pediatric heart transplant recipients: Correlation of histology, cardiovascular magnetic resonance, and clinical phenotype

Abstract: Fibrosis is commonly described in heart allografts lost late after transplantation. CMR-derived ECV is a validated measure of DMF in native adult hearts that may predict heart failure and mortality. We explored associations of ECV with histologic myocardial fibrosis and clinical features after pediatric heart transplantation. Twenty-five recipients (7.0±6.3 years at transplant and 10.7±6.5 years post-transplant) were prospectively recruited for CMR and BNP measurement at the time of surveillance biopsy. All ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
(140 reference statements)
1
9
0
Order By: Relevance
“…In a prior study of obese diabetic and nondiabetic adolescents, BMI was also associated with ECV, even after adjusting for HTN (33). These subtle alterations to the myocardial interstitium preceded LV dysfunction, as has been shown in the pediatric heart transplant population (34). Our findings are consistent with prior studies in other populations, demonstrating changes to the extracellular matrix with obesity.…”
Section: Discussionsupporting
confidence: 90%
“…In a prior study of obese diabetic and nondiabetic adolescents, BMI was also associated with ECV, even after adjusting for HTN (33). These subtle alterations to the myocardial interstitium preceded LV dysfunction, as has been shown in the pediatric heart transplant population (34). Our findings are consistent with prior studies in other populations, demonstrating changes to the extracellular matrix with obesity.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, CMR has shown substantial promise for detection of graft dysfunction in adult heart transplant recipients [ 21 , 23 , 24 , 28 , 37 , 49 53 ], however, data are quite limited in PHT [ 37 , 38 , 40 , 43 , 54 , 55 ]. Our study demonstrates the safety and feasibility of comprehensive CMR with regadenoson stress perfusion for graft surveillance in PHT.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that, BNP may have utility in monitoring of cardiac performance with the caveat that a low hematocrit can also affect its levels. A correlation between diffuse myocardial fibrosis which is considered secondary to microvascular coronary disease after HT and BNP level has been reported [18]. Linear correlations between worsening of global longitudinal strain with high BNP levels, end-diastolic left ventricular volume, and pulmonary capillary wedge pressure have also been reported [19].…”
Section: Bnp Level and Cardiac Allograft Vasculopathymentioning
confidence: 96%